2014
DOI: 10.3906/biy-1303-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterotic grouping and patterning of quality protein maize inbreds based on genetic and molecular marker studies

Abstract: An investigation was done to study the heterotic grouping and patterning in quality protein maize inbreds. Biochemical screening resulted in the choice of 3 inbreds each with high (UQPM 2, UQPM 4, and UQPM 21) and low (UQPM 18, UQPM 19, and UQPM 20) lysine and tryptophan contents respectively for genetic studies using diallel analysis. UQPM 20 × UQPM 18 was notable as it possessed high standard heterosis and specific combining (sca) effect for grain yield, protein, tryptophan, and lysine. Based on yield sca, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 48 publications
(56 reference statements)
1
19
1
Order By: Relevance
“…No previous reports were found that report the use of EST-SSR markers for analyzing genetic relationships in maize; however, the average PIC value determined in our study was higher than some reported results in the literature based on genomic SSR markers, such as those reported by Wende et al (2013) (0.54) and Heckenberger et al (2002) (0.58), and below the values found in studies by Rajendran et al (2014) (0.81) and Garcia et al (2004) (0.89). However, it is important to note that estimates of PIC are inherent to the loci analyzed, as well as the structure of the studied population.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…No previous reports were found that report the use of EST-SSR markers for analyzing genetic relationships in maize; however, the average PIC value determined in our study was higher than some reported results in the literature based on genomic SSR markers, such as those reported by Wende et al (2013) (0.54) and Heckenberger et al (2002) (0.58), and below the values found in studies by Rajendran et al (2014) (0.81) and Garcia et al (2004) (0.89). However, it is important to note that estimates of PIC are inherent to the loci analyzed, as well as the structure of the studied population.…”
Section: Resultscontrasting
confidence: 56%
“…The PIC shows the informativeness of loci and their potential to detect differences between genotypes based on their genetic relationships (Rajendran et al, 2014). According to Botstein et al (1980), a locus can be classified as highly informative when the value of PIC is greater than 0.5, moderately informative when the value ranges from 0.5 to 0.25, and not informative when less than 0.25.…”
Section: Resultsmentioning
confidence: 99%
“…Heterosis is also affected by the interaction among the genes. The heterotic grouping and pattern are connected with gene interaction (Rajendran et al, 2014), but due to lack of approaches it is difficult to distinguish the gene interactions for the purpose of genetic diversity analysis. The strategy could be to improve the heterotic response by recycling and selecting superior lines within/ between groups with moderate distance, based on hybrid performance and their GCA effect as this may throw better segregants.…”
Section: Resultsmentioning
confidence: 99%
“…In India, six parental inbreds were classified into three heterotic groups based on their specific combining ability for yield under low soil pH. In this case, the superior heterotic pattern was flint × dent [107].…”
Section: Heterosis Heterotic Patterns and Heterotic Groups For Maizmentioning
confidence: 99%
“…The application of these methods could be useful in developing high-yielding maize genotypes with tolerance to low soil pH. Several research studies [12,13,15,[103][104][105][106][107] have been conducted during the past few years under low soil pH conditions using conventional methods (including combinability and heterotic grouping) with the goal of developing high-yielding and tolerant maize genotypes. Despite the efforts and progress made by researchers, the grain yield loss of maize due to low soil pH is still very high.…”
Section: Heterosis Heterotic Patterns and Heterotic Groups For Maizmentioning
confidence: 99%